CIRS-LAS – a novel approach to increase transparency in laboratory animal science for improving animal welfare by reducing laboratory animal distress - Enkelmann, Astrid; Bischoff, Sabine J. (Frontiers in Veterinary Science, 2023)
The 3R principle is highly topical in animal-based research. These include, above all, new scientific methods for conducting experiments without an animal model, by using non-animal models (Replace), reducing the number of laboratory animals (Reduction) or taking measures to keep the stress on the laboratory animal as low as possible (Refinement). Despite numerous modern alternative approaches, the complete replacement of animal experiments is not yet possible. The exchange in the team about the daily work with laboratory animals, about open questions and problems, contributes to a reflection of one's own work and to a better understanding of the work of the others. CIRS-LAS (Critical Incident Reporting System in Laboratory Animal Science) represents a reporting system for incidents in laboratory animal science. It is urgently needed because the lack of transparency about incidents leads to the repetition of failed experiments. Negative experiences from animal-based experiments are often not mentioned in publications, and the fear of hostility is still very high. Therefore, a constructive approach to errors is not a matter of course. To overcome this barrier, CIRS-LAS was created as a web-based database. It addresses the areas of reduction and refinement of the 3R principle by providing a platform to collect and analyze incidents. CIRS-LAS is open to all individuals working with laboratory animals worldwide and currently exists with 303 registered members, 52 reports, and an average of 71 visitors per month. The development of CIRS-LAS shows, that an open and constructive error culture is difficult to establish. Nevertheless, the upload of a case report or the search in the database leads to an active reflection of critical occurrences. Thus, it is an important step towards more transparency in laboratory animal science. As expected, the collected events in the database concern different categories and animal species and are primarily reported by persons involved in an experiment. However, reliable conclusions about observed effects require further analysis and continuous collection of case reports. Looking at the development of CIRS-LAS, its high potential is shown in considering the 3R principle in daily scientific work.